Late Pleistocene Deglaciation History at Point Partridge, Central Whidbey Island, Washington - Carlstad, Cynthia A. (Western CEDAR, 1992)
The study area contains a record of deglaciation events that has not been recognized elsewhere in the Puget Lowland. This record includes both subaerial outwash and glaciomarine deposition. The geologic history of the study area during recession of the Vashon ice sheet is marked by the following events: Deposition of a kame delta complex from grounded ice probably located in Penn Cove and west of Point Partridge. This delta complex was built into marine water with a sea-level at approximately 55 meters. Eventually, ice drained by the outwash streams stagnated in the Point Partridge kettle region. Isostatic rebound of the depressed land surface caused relative sea-level to drop as the ice continued to become thinner. Deposition of sand and gravel from outwash streams ceased as the ice continued to thin and eventually floated, depositing glaciomarine drift below approximately 37 meters. Narrow marine terraces were carved into Vashon till and Partridge outwash around the perimeter of Penn Cove. In addition to these events, the relationship between the Partridge outwash and Everson glaciomarine drift is described. Partridge outwash is an Everson Interstade unit, deposited by meltwater streams in a marine environment.